2022
DOI: 10.1111/nuf.12728
|View full text |Cite
|
Sign up to set email alerts
|

Student perspectives on potential sources of trauma exposure during nursing school

Abstract: Adverse effects of events experienced by nursing students as harmful during nursing school have included moral distress, prolonged grief reactions, secondary traumatic stress, and anxiety and depression during nursing school. Nursing student perceptions of potential sources of trauma exposure also known as potentially traumatic events (PTEs) during nursing school are lacking in the literature. The purpose of this study was to describe nursing students' perceptions of potential sources of trauma exposure during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Nursing students' empathy for the traumatized individual and/or learning about the trauma experienced by the individual may cause the development of secondary traumatic stress symptoms (14,15). It is known that students who experience secondary traumatic stress have difficulty in showing compassion and an empathic approach to themselves and patients and do not want to do the nursing profession (7,10,14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nursing students' empathy for the traumatized individual and/or learning about the trauma experienced by the individual may cause the development of secondary traumatic stress symptoms (14,15). It is known that students who experience secondary traumatic stress have difficulty in showing compassion and an empathic approach to themselves and patients and do not want to do the nursing profession (7,10,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students' empathy for the traumatized individual and/or learning about the trauma experienced by the individual may cause the development of secondary traumatic stress symptoms (14,15). It is known that students who experience secondary traumatic stress have difficulty in showing compassion and an empathic approach to themselves and patients and do not want to do the nursing profession (7,10,14,15). In this study, which was conducted to examine the relationship between secondary traumatic stress level and perceived care behaviors of nursing students, it was found that the mean STSS score of the students was 32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ncivility and bullying are pervasive issues affecting novice nurse educators and clinical nurses alike. [1][2][3] The phrase "nurses eat their young" is still commonly heard in current working environments of nurses. 4 Incivility is defined as "rude or unsociable speech or behavior" and refers to disrespectful and impolite behaviors and comments.…”
mentioning
confidence: 99%
“…Incivility and bullying are pervasive issues affecting novice nurse educators and clinical nurses alike 1-3. The phrase “nurses eat their young” is still commonly heard in current working environments of nurses 4…”
mentioning
confidence: 99%